2014
DOI: 10.1016/j.jcomdis.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Semantic effects in sentence recall: The contribution of immediate vs delayed recall in language assessment

Abstract: The reader will be able to: (i) define the difference between immediate and delayed sentence recall and different types of distractors, (ii) explain the utility of immediate and delayed recall sentence recall in language assessment, (iii) discuss suitability of delayed recall for the assessment of semantics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
2
11
1
Order By: Relevance
“…It could also be that the linguistic stimuli in this study may not have been sensitive enough to elicit a semantic plausibility effect. The latter explanation seems unlikely because similar sentences in terms of number of words and syntactic complexity have been used previously in the neurotypical and aphasia literature [31,32,37]. Our findings also differ from Newcombe and Marshall [34], the only other study of sentence recall in possibly latent aphasia that we are aware of.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…It could also be that the linguistic stimuli in this study may not have been sensitive enough to elicit a semantic plausibility effect. The latter explanation seems unlikely because similar sentences in terms of number of words and syntactic complexity have been used previously in the neurotypical and aphasia literature [31,32,37]. Our findings also differ from Newcombe and Marshall [34], the only other study of sentence recall in possibly latent aphasia that we are aware of.…”
Section: Discussioncontrasting
confidence: 66%
“…Accuracy is the standard way of investigating sentence recall. While past research [32,38] showed that it is discriminatory in relatively more severe forms of mild aphasia, such as anomic, accuracy as a measure on its own may not distinguish between latent aphasia and neurotypical controls. This finding highlights the importance of temporal speech measures in revealing subtle language deficits not only as a result of stroke [16,27] but also other neurological conditions, non-progressive and progressive [83].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Evidence is available for both children and adults and for typologically different languages (English, Arabic, Czech; e.g., Miller & Isard, 1963;Polišenská et al, 2015;Valian et al, 2006;Wallan et al, 2011). For example, in a delayed recall task, Polišenská, Chiat, Comer and McKenzie (2014) demonstrated that plausibility improved recall in adults and six-year-old children, and that this effect increased with task difficulty. Plausible and implausible sentences encode different situations, with plausible sentences describing situations more likely to have occurred in the real world and therefore to have been experienced and encoded by the listener.…”
Section: Immediate Sentence Repetitionmentioning
confidence: 99%